Use of Detomidine Oromucosal Gel for Alleviation of Acute Anxiety and Fear in Horses: A Pilot Study - Dai, Francesca; Rausk, Julia; Aspegren, John; Huhtinen, Mirja; Cannas, Simona; Minero, Michela (Frontiers in Veterinary Science, 2020)
The aim of this randomized, double-blind, placebo-controlled, parallel group clinical field study was to evaluate the effect of Detomidine oromucosal gel in alleviating anxiety and fear in horses. Sixteen horses with a history of acute anxiety and fear associated with firework-related noise entered the study. On New Year’s Eve, 8 horses were treated with 30 µg/kg Detomidine gel and 8 horses with placebo gel. When fireworks were present, 75% (6/8) of the Detomidine-treated horses were scored by their owners as having a good or excellent treatment effect on anxiety and fear, while 50% (3/6) of horses receiving placebo were scored to have a good effect. Horses’ behavior was video-recorded and assessed with a focal animal continuous method by a treatment-blind expert observer. Results showed that when fireworks were present walking behavior decreased significantly (p<0.05) after treatment with Detomidine and that horses of the Placebo group, overall, showed more restlessness, vocalization and signs of colic (Wilcoxon matched-pairs test on the first PC, p=0.007). This study indicates that Detomidine oromucosal gel can be used to alleviate acute noise-related anxiety and fear in horses, but larger treatment groups are needed to confirm the results.